Especificidade e sensibilidade do Questionário de Transtorno do Desenvolvimento da Coordenação - Brasil para crianças de 8 a 10 anos - Souza, Thamires da Fonseca de (2016)
Different instruments meet the criteria of the Manual Diagnostic and Statistical of Mental Disorders (DSM) for the diagnosis of Developmental Coordination Disorder (DCD) have been used by researchers. Among them, the most recognized and employed questionnaire today for screening is the Developmental Coordination Disorder Questionnaire (DCDQ), a questionnaire for parents developed in Canada. This was translated and adapted to Brazilian culture, however its scoring system was not standardized for Brazilian children. Therefore, this study aimed to evaluate the sensitivity and specificity of the questionnaire to a group of children aged 8, 9 and 10 years using as gold standard the Movement Assessment Battery for Children Test (Mabc-2) engine test also identify the cutoff point for each specific age and correlate the scores of both tests between gender and between economic classes. It is a descriptive study transversal - exploratory, with a quantitative approach. The participants were 100 children enrolled in the municipal school system of Rio Claro -SP, where had their motor skills evaluated using the DCDQ-Brazil and Mabc-2, and their socioeconomic conditions verified by Criterion Brazil. The data collected were subjected to statistical analysis of association and the cutoff set by the Youden index and Roc curve (Receiver Operator Characteristic). The results reveal the DCDQ-Brazil does not have satisfactory validity to the Brazilian context analyzed in the sample at the ages of 8 and 10 years the ages of 8 and 10 years, with its higher cutoff points the cutoff points defined in this study, in a proportion ranging 4-7 points. Also found, contrary to what area of the studies show, girls and boys do not have significant difference when evaluated in DCDQ-Brazil and Mabc-2, and no association between the results of the instruments and the socioeconomic classification of participants was detected, suggesting socioeconomic status does not imply engine performance and incidence of DCD. It was possible to ascertain the use of Mabc-2 instruments and DCDQ-Brazil together enables check for data favor the evaluation of the specificity and sensitivity of DCDQ-Brazil for a group of children aged 8 and 10 years. For future research it is suggested further data on the age of 9 years to use the Developmental Coordination Disorder Questionnaire form adapted to Brazilian children between 8 to 10 years promoting the early identification process of the DCD.